Composite resin and silver cavity filling for the canine teeth fracture in Puma (Puma concolor) - Jayaseelan, Kavitha; Ramli, Mat Naim; Radzi, Rozanaliza; Razlan, Mira Farhana; Che Amat, Azlan (Chiang Mai University - Faculty of Veterinary Medicine, 2025)
A 12-year-old captive Puma concolor was found to have tooth fractures on both maxillary canines (104, 204) and the left mandibular canine (304), as well as decay on the right maxillary canine (104). The puma was losing weight gradually, but was peaceful, vigilant, and receptive when observed from a distance. The puma suffered from generalised osteopenia as well as a right mid-humeral fracture. The blood result showed hypocalcaemia, although the other parameters were within normal limits. Upon a dental examination, the puma was diagnosed with a severe crown fracture caused by nutritional secondary hyperparathyroidism due to an imbalanced diet and a lack of vitamin D due to a lack of sunlight exposure, resulting in hypocalcaemia. All three dental crown fractures exposed the pulp chamber. Dental restoration and filling were performed using either a composite resin or silver (amalgam) filling to keep the functional teeth, relieve discomfort, and improve quality of life. Animal is clinically healthy post-operatively and has improved quality of life with no pain and normal appetite.